Hydrogen isotope exchange experiments in high entropy alloy WMoTaNbV. (March 2023) - Vuoriheimo, T.; Liski, A.; Jalkanen, P.; Ahlgren, T.; Mizohata, K.; Heinola, K.; Zayachuk, Y.; Tseng, K.–K.; Tsai, C.–W.; Yeh, J.–W.; Tuomisto, F.
Highlights: Fusion fuel removal from High Entropy Alloy material. Implanted deuterium replaced with protium by annealing in hydrogen gas. Deuterium removal very effective near the surface. In the bulk deuterium is not removed as efficiently. High H retention found to be a problem due to permeation and deep trapping. Abstract: Plasma–facing components in future fusion reactors must endure high temperatures as well as high fluxes and fluences of high energy particles. Currently tungsten has been chosen as the primary plasma-facing material due to its good thermal conductivity, low erosion rate and low fuel retention. Materials with even better properties are still being investigated to be used in reactor regions with demanding plasma conditions. High entropy alloys (HEA) are a new class of metallic alloys and their exploitation in fusion applications has not been widely studied. In this work, the hydrogen isotope exchange effect in an equiatomic HEA containing W, Mo, Ta, Nb, and V was studied. Deuterium was implanted into HEA samples with 30 keV/D energy and the HEA and reference samples were annealed in H2 atmosphere and in vacuum at various temperatures up to 400 °C, respectively. The near-surface D concentration profiles were measured with ERDA and the isotope exchange was observed to remove over 90 % of the trapped deuterium from the implantation region at temperatures above 200 °C. TDS was used to measure retention deeper in the bulk in which the reduction of trapped deuterium was significantly lower. High total retention of H was found in the bulk after H2 atmosphere annealing which indicates permeation and deep trapping of H in the material.